2017
DOI: 10.1093/scan/nsx022
|View full text |Cite
|
Sign up to set email alerts
|

Neurological evidence for the role of construal level in future-directed thought

Abstract: The ability to mentally represent future events is a significant human psychological achievement. A challenge that people encounter is that they often lack detailed specifics about distant relative to near future events. Construal level theory proposes that people represent distant future events by their abstract and essential features—a process referred to as high-level construal. As events become temporally proximal, people represent events by their increasingly available and reliable concrete and idiosyncra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 76 publications
(136 reference statements)
3
25
0
Order By: Relevance
“…We note that the manipulations and data of the construal level and temporal distance tasks have been previously reported in Stillman et al (2017) That paper reported the results based on these two tasks, showing that visualizing the distant (vs. near) future recruited overlapping regions as high‐ (vs. low‐) level construal, and thus providing the first neurological evidence for the distance‐construal link. The present paper thus includes a reanalysis of these previously published data in addition to color of imagery data (which were not previously reported) to provide the first neurological evidence for distinguishing BW versus color imagery, and their relationships with temporal distance versus proximity and high‐level versus low‐level construal, respectively.…”
Section: Manipulations Of Color Construal and Distancesupporting
confidence: 75%
See 3 more Smart Citations
“…We note that the manipulations and data of the construal level and temporal distance tasks have been previously reported in Stillman et al (2017) That paper reported the results based on these two tasks, showing that visualizing the distant (vs. near) future recruited overlapping regions as high‐ (vs. low‐) level construal, and thus providing the first neurological evidence for the distance‐construal link. The present paper thus includes a reanalysis of these previously published data in addition to color of imagery data (which were not previously reported) to provide the first neurological evidence for distinguishing BW versus color imagery, and their relationships with temporal distance versus proximity and high‐level versus low‐level construal, respectively.…”
Section: Manipulations Of Color Construal and Distancesupporting
confidence: 75%
“…As described in Stillman et al (2017), both high‐level construal and distant future events activated regions in the mPFC and bilateral middle temporal gyrus, whereas low‐level construal and near‐future activated regions of the precuneus.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…One of the regions found in this network was the precuneus, showing higher positive functional connectivity with the seed region in its posterior part, and negative correlations in its superior part in the coherent compared to the incoherent narrative group. The precuneus plays an important role in high cognitive functions 42 and is involved in retrieval of past representations and in simulating future scenarios 43 as well as in meta-cognition 44 , all of which are critically required for coherent narrative construction. Its activation during the processing of a continuous story has previously been interpreted as being involved in the holistic representation of meaningful pieces of information 4546 and their segmentation 18,27,46 .…”
Section: Discussionmentioning
confidence: 99%